Twenty years of BIMSTEC promoting regional cooperation and integration in the Bay of Bengal region - De, Prabir (Routledge, 2020)
This book reviews the past and provides new strategies to help BIMSTEC achieving a new paradigm of integration. It primarily deals with the regional cooperation and integration issues, and assesses policy priorities, effectiveness, implementation imperatives and challenges. Each chapter in this book tries to capture essential features of the crosscutting issues and attempts to draw some policy implications. The subject of this book will be of special interests to policy planners, development organisations, academicians, researchers as well as potential investors. Please note: T & Fdoes not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka